2004
DOI: 10.1109/twc.2004.837276
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Human Activity on Wide-Band Characteristics of the 60 GHz Indoor Radio Channel

Abstract: Abstract-This paper presents propagation measurements in the presence of human activity for a 60 GHz channel. Series of 40-min-long measurements of the channel impulse response have been recorded with a sampling period of 1.6 ms, for a total duration of about 20 h. During measurements, the human activity (between zero and 15 persons) was observed with a video camera. The obstruction phenomenon due to the human bodies is characterized in duration and amplitude from the propagation characteristics (attenuation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(156 citation statements)
references
References 11 publications
5
139
2
Order By: Relevance
“…Human bodies are also relevant link shadowing objects both in the indoor and outdoor context. Experimental works of characterizing the human body shadowing in indoor scenarios show up to 20 dB excess losses [47], [48]. Shadow duration: The time period where the link shadowing persists affects the link outage performance significantly.…”
Section: Large-scale Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human bodies are also relevant link shadowing objects both in the indoor and outdoor context. Experimental works of characterizing the human body shadowing in indoor scenarios show up to 20 dB excess losses [47], [48]. Shadow duration: The time period where the link shadowing persists affects the link outage performance significantly.…”
Section: Large-scale Modelsmentioning
confidence: 99%
“…For example, temporal variations induced by the moving people leads up to 50 ms of coherence time of a radio channel at 60 GHz [49], and up to 3 ms at 30 GHz [50], [51]. On the other hand, [47] shows that the human body shadowing lasts for a median period of 100 ms in a scenario with one-to-five person walking and for 300 ms with 11-15 persons. A similar analysis for a crowded aircraft cabin [48] reports maximum and median depth durations of 8000 and 500 ms. Delay spread: Delay spread is another important characteristics parameter that determines the intersymbol interference in single-carrier transmission and the frequency-flatness of the subcarriers in multi-carrier physical layer schemes [20].…”
Section: Large-scale Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of multipath for directional mm wave links [23], [32], [33] means that link budget calculations for a simple additive white Gaussian noise channel model are reasonably accurate for a directional LOS link. The susceptibility of mm wave links to blockage due to their weak diffraction characteristics is well known [23], [34], and the effect of human movement is investigated in [35], [36], but their impact on the network performance has not been studied previously. Many deterministic and statistical mm wave propagation models have been proposed based on channel measurement studies [25], [30], [37], but many of these focus on omnidirectional transmission (and possibly directional reception).…”
mentioning
confidence: 99%
“…Especially in indoor scenarios, walking humans may frequently block the wireless links, which generates more problems than stable objects. It is reported that the human body can attenuate the signal by more than 20 dB [4], which is hard to overcome by using only beamforming techniques, particularly when considering power regulations and potential health consequences. For instance, it has been shown in [4] that the channel is thus unavailable for about 1-2 % of the time in the presence of one to five persons in a room.…”
Section: Introductionmentioning
confidence: 99%